An empirical analysis of the constructs of Fundamentals of Care Framework using structural equation modelling. (22nd July 2022) - Blackman, Ian; Mudd, Alexandra
Abstract: Aim: First, to identify which aspects of missed care accurately define the integration of care and context of care dimensions of the Fundamentals of Care Framework. Second, to test the Framework for validity and reliability and lastly, to explore how leadership influences care integration. Design: A non‐experimental research design using self‐audit data collected information about variations in nursing care as exemplars for dimensions of the Framework. Methods: A multi‐variate approach using path analysis was used to apply the consensus scores of 3079 Australian residential care nurses and carers to define the dimensions of the Framework. Results/Findings: In the Australian residential care setting, the factors that define both the contexts of care and the integration of care dimensions constructs are now empirically established. The most direct predictor for the integration of care dimension arises from both the leadership and resource allocation variables, while the remaining context of care factors have indirect but significant effects. The integration of psychosocial care in the residential care sector is not influenced by any of the Framework's context‐based factors. Conclusion: The component variables of the Framework show both good reliability and convergent validity. These findings confirm a predictive relationship exists between the elements of the context of care and the different types of nursing activities that form the integration of the care dimension, including organizational leadership.